Kesulitan Belajar Online Ilmu Nahwu Pada Mahasiswa Pendidikan Bahasa Arab - Rappe, Rappe; Dian Angraeni, Andi (Shaut al Arabiyyah, 2024)
This research was conducted to determine the difficulties of online learning of student nahwu science and the efforts made in overcoming these learning difficulties. This research uses a quality approach with a type of case study research. The subject of the study was a student of the Arabic Language Education Study Program UIN Alauddin Makassar. Data collection was carried out using questionnaire instruments and guided free interview guidelines. Data analysis uses Milles and Huberman’s model which consists of reduction, presentation, and drawing conclusions. The results of the research obtained are the difficulty of learning online nahwu science faced by students consisting of difficulty understanding the material due to lack of concentration, unstable networks, lack of references, limited media use, and the environment. The efforts that students have made in overcoming these difficulties are trying to relearn papers, creating study groups together, learning from electronic books, changing data packages or changing locations for lectures, and downloading the I’rob application.